Assessment of nuclear maturation and subsequent in vitro embryo development of caprine oocytes with different supplementations in maturation medium - YADAV, PARUL; KHARCHE, S D; GOEL, A K; JINDAL, S K; GOEL, PUJA (The Indian Journal of Animal Sciences, 2013)
The maturation medium and selection of protein supplements, growth factors, antioxidants and hormones for IVM play an important role in subsequent in-vitro fertilization and in-vitro embryo development. The objective of the present experiment was to study the effect of exogenous addition of hormones, epidermal growth factor (EGF), insulin and ßmercaptoethanol into the maturation medium for in-vitro maturation of caprine oocytes. A total of 3753 Cumulus oocyte complexes (COCs) were collected from slaughtered goat ovaries, randomly divided and matured into following treatment groups. Group 1 (control): TCM-199 medium containing 10% newborn calf serum (NCS) and 3mg/ml BSA used as base medium, group 2: base medium supplemented with FSH (5μg/ml), LH (5μg/ml) and estradiol-17ß (1μg/ml), group 3: base medium supplemented with insulin (50ng/ml), group 4: base medium supplemented with FSH (5μg/ml),LH (5μg/ml), estradiol-17ß (1μg/ml) and epidermal growth factor (EGF; 10ng/ml), group 5: base medium supplemented with FSH (5μg/ml), LH (5μg/ml), estradiol-17ß (1μg/ml) and ß-mercaptoethanol (50mM/ml) and group 6: COCs were matured in a base medium supplemented with FSH (5μg/ml), LH (5μg/ml), estradiol-17ß (1μg/ml) and insulin (50 ng/ml). After maturation, 1, 540 oocytes from different groups were assessed for the evidence of nuclear maturation. Remaining 2,213 oocytes from different maturation group were allowed for in vitro fertilization and subsequent in vitro embryo development. The nuclear maturation rates in groups 1 to 6 were 33.6%, 38.0%, 39.7%, 60.0%, 37.4%, and 44%, respectively. The cleavage rate and morula production rate in groups 1 to 6 were 10%, 24%, 27%, 25%, 31%, 28% and 5.12%, 15.6%, 5.55%, 10.41%, 13.3%, 5.49% respectively. Statistical analysis (ANOVA) after arcsin transformation revealed that the maturation rate in group 4 was statistically significant (P <0.05) as compared with other groups. ANOVA also revealed that morula development was significantly higher in group 2, group 4 and group 5 as compared to group 1, group 3 and group 6. The results suggested that the supplementation of EGF along with hormones in maturation medium significantly enhances the in-vitro maturation rate of caprine oocytes. These results also indicated that the supplementation of hormones, hormones with ß-mercaptoethanol, hormones with insulin in base medium have significantly higher embryo development competence in comparison with other groups.